2016
DOI: 10.1093/eurheartj/ehw226
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variations in the PARADIGM-HF heart failure trial

Abstract: AimsThe globalization of clinical trials has highlighted geographic variations in patient characteristics, event rates, and treatment effects. We investigated these further in PARADIGM-HF, the largest and most globally representative trial in heart failure (HF) to date.Methods and resultsWe looked at five regions: North America (NA) 602 (8%), Western Europe (WE) 1680 (20%), Central/Eastern Europe/Russia (CEER) 2762 (33%), Latin America (LA) 1433 (17%), and Asia-Pacific (AP) 1487 (18%). Notable differences incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
105
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(114 citation statements)
references
References 24 publications
6
105
1
2
Order By: Relevance
“…16 In addition, a comparison with other randomized clinical trial and registry data for Japanese patients with HFrEF, revealed a similar trend of lower BP while receiving the standardof-care background HF therapies. 12, 13 Similarly, the lower rate of ischemic etiology for HF in PARALLEL-HF relative to that reported in PARADIGM-HF was in line with earlier observations from this geographic region.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…16 In addition, a comparison with other randomized clinical trial and registry data for Japanese patients with HFrEF, revealed a similar trend of lower BP while receiving the standardof-care background HF therapies. 12, 13 Similarly, the lower rate of ischemic etiology for HF in PARALLEL-HF relative to that reported in PARADIGM-HF was in line with earlier observations from this geographic region.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, enrolled patients were largely similar to those in PARADIGM-HF, including those of the Asia-Pacific subgroup of PARADIGM-HF previously reported in the subgroup analysis by Kristensen et al, which showed that sacubitril/valsartan was equally effective in reducing the risk of CV death and HF hospitalization compared with enalapril. 16 The results of PARALLEL-HF are expected by 2019 and will verify whether sacubitril/valsartan provides similar improvements in clinical outcomes in Japanese patients with HFrEF as has been observed in PARADIGM-HF.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Например, по данным исследования PARADIGM-HF частота назначений антагонистов минералокорти-коидных рецепторов существенно отличалась в ре-гионе «Центральная/Восточная Европа -Россия» от регионов «Северная Америка» и «Западная Европа». В целом наиболее современная, основанная на доказа-тельствах терапия ХСН назначалась чаще в регионах «Северная Америка» и «Западная Европа» [8]. В ази-атском регистре ХСН было также обнаружено наличие региональных различий в терапии ХСН, при этом вы-явлено влияние на вероятность соблюдения рекомен-даций уровня дохода в том или ином регионе [9].…”
unclassified